Тrends In Creative Neologization In The Language Of Modern Science - Kushakov Shuxrat Saliyevich (Peerian Journals Publishing, 2023)
This article analyzes the content of trends in creative neologization in the language of modern science, the issues of word-formation practice in the modern science language are considered. The trend of neologization in post-non-classical sciences is analyzed. The features of the author's neologization in science are revealed. It is noted that the author's neologization is the main way of linguistic-semiotic expression of new properties, aspects and characteristics of the object under study. As an illustration, work on neologization in such areas of post-non-classical sciences as the theory of virtuality and synergetics is considered
Keywords: Post-non-classical science; author’s neologization